UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA METODE EXAMPLE DAN NON EXAMPLE PADA SISWA KELAS IX.1 SMPN 1 SASAK RANAH PASISIA - amzar amzar (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the results of student learning IX.1SMPN Class 1 Sasak Sphere Pasisia in subjects Indonesian sub Explaining the various events by the sentence jelasditemukan that results for students in the subjects of Indonesian sub Reported verbally various events using clear sentences are still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in subjects Indonesian sub Describes various events using clear sentences through And Non Example Example Methods in Class 1 Sasak Sphere IX.1SMPN Pasisia West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 24 students Grades 1 Sasak Sphere IX.1SMPN Pasisia. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the method and Non Example Example can improve student learning outcomes in subjects Indonesian sub Explaining the various events by the sentence that jelasdi SMP 1 Sasak Sphere Pasisia. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 49.33 (less) increased to 82.63 (good) with an increase of 33.29Keywords: Learning Outcomes, Indonesian, Methods And Non Example Example